Border walls and smuggling spillovers - Getmanski, Anne (2019)
A growing number of states are erecting physical barriers along their borders to stem the illicit flow of goods and people. Though border fortification policies are both controversial and politically salient, their distributional consequences remain largely unexplored. We study the impact of a border wall project on smuggling in Israel. We use the initial phase of the wall construction to causally estimate spillover effects on cross-border smuggling, especially vehicle theft. We find a large decrease in smuggling of stolen vehicles in protected towns and a similar substantial increase in not-yet-protected towns. For some protected towns, fortification also arbitrarily increased the length of smuggling routes. These township-level shocks further deterred smuggling (6% per kilometer). Our findings suggest that border fortification may have uneven distributional consequences, creating unintended winners and losers